2008
DOI: 10.1093/ndt/gfn151
|View full text |Cite
|
Sign up to set email alerts
|

Calcium load during administration of calcium carbonate or sevelamer in individuals with normal renal function

Abstract: Intake of calcium carbonate compared to placebo in contrast to sevelamer in healthy individuals was associated with increased total urinary calcium excretion indicating an increased calcium load due to increased intestinal calcium absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Dosing with two calcium carbonate tablets (800 mg of elemental calcium) resulted in a decrease in urinary phosphorus excretion of 31 mg (1.0 mmol) compared with control, whereas six calcium acetate tablets reduced urinary phosphorus by 132 mg (4.3 mmol) [22 mg (0.71 mmol) per tablet]. In another study21 the calculated reduction in 24-h urinary excretion of phosphate after 6 days of treatment was 66 mg (2.1 mmol) per 1000 mg of elemental calcium compared with 32 mg (1.0 mmol) per 1000 mg of SH.…”
Section: Discussionmentioning
confidence: 96%
“…Dosing with two calcium carbonate tablets (800 mg of elemental calcium) resulted in a decrease in urinary phosphorus excretion of 31 mg (1.0 mmol) compared with control, whereas six calcium acetate tablets reduced urinary phosphorus by 132 mg (4.3 mmol) [22 mg (0.71 mmol) per tablet]. In another study21 the calculated reduction in 24-h urinary excretion of phosphate after 6 days of treatment was 66 mg (2.1 mmol) per 1000 mg of elemental calcium compared with 32 mg (1.0 mmol) per 1000 mg of SH.…”
Section: Discussionmentioning
confidence: 96%
“…6 Lanthanum carbonate and sevelamer HCl are commercially available calcium-free binders that provide a lower calcium load and may be advantageous in already calcified patients or patients with higher-than-target calcium levels. [15][16][17] Sevelamer in particular slows vascular calcification in pre-dialysis and dialysis patients, and may target additional risk factors. 16,18,19 Thus, sevelamer lowers LDL cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [19] reported Ca Abs over a range of intake of 1,200-3,000 mg/day normally distributed over 3 meals per day with the results depicted as 'Heidelberg data' in figure 1 . These data were obtained from normal subjects so that the coordinates of the 3 points in figure 1 indicate virtually perfect correlation with the modeled relationships, since they fall on the modeling line for normal C p D 3 2OH of 30-40 pg/ml [20,21] .…”
Section: Calcium Absorptionmentioning
confidence: 99%